2007
DOI: 10.1126/science.1139531
|View full text |Cite|
|
Sign up to set email alerts
|

An Evolutionarily Conserved Mechanism Delimiting SHR Movement Defines a Single Layer of Endodermis in Plants

Abstract: Intercellular protein movement plays a critical role in animal and plant development. SHORTROOT (SHR) is a moving transcription factor essential for endodermis specification in the Arabidopsis root. Unlike diffusible animal morphogens, which form a gradient across multiple cell layers, SHR movement is limited to essentially one cell layer. However, the molecular mechanism is unknown. We show that SCARECROW (SCR) blocks SHR movement by sequestering it into the nucleus through protein-protein interaction and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
599
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 519 publications
(653 citation statements)
references
References 28 publications
45
599
2
7
Order By: Relevance
“…In addition, our pair-wise analysis revealed that only two pairs showed protein-protein interactions. We confirmed the interaction between SHR and SCR, which plays an important role in the regulation of SHR movement as recently reported (Cui et al 2007, Welch et al 2007 (Fig. 7).…”
Section: Interaction Among Gras Proteins In Y2h Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, our pair-wise analysis revealed that only two pairs showed protein-protein interactions. We confirmed the interaction between SHR and SCR, which plays an important role in the regulation of SHR movement as recently reported (Cui et al 2007, Welch et al 2007 (Fig. 7).…”
Section: Interaction Among Gras Proteins In Y2h Assaysupporting
confidence: 91%
“…Surprisingly, most GRAS proteins show no interaction among the members, except for SCR, SHR, and SCL23. Recent studies revealed that the protein-protein interaction between SCR and SHR is crucial to regulate the SHR movement (Cui et al 2007, Welch et al 2007. In this study, we not only confirmed the interaction between SCR and SHR, but also identified a novel SHR-interacting protein, SCL23, which is the most closely related to SCR among GRAS members.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the SHR protein moves one cell layer away from its point of production, to the endodermis. This cell-to-cell movement is under the control of the SCR protein, which interact directly with SHR and sequesters it in the nuclei of the endodermal cells (Fig 18C, D) (Cui et al, 2007). Misexpression of SHR in the SCR domain results in extra layers of endodermis, probably by reiterating the emission of a positional signal, which in normal development is communicated only from the vascular cylinder to just one cell layer above.…”
Section: Radial Patterning In the Ground Tissuementioning
confidence: 99%
“…Therefore, the SHR product seems to be the key signal in a short-range induction mechanism and in moving just one layer triggers endodermal differentiation from a cortical ground state adjacent to its vascular origin. The C2H2 zinc-fi nger protein JACKDAW (JKD) has been identifi ed as partner and target of SHR and SCR (Cui et al, 2007;Welch et al, 2007). JKD expression is initiated during the globular stage in a SHR/SCR independent way, but its continued expression depends on the presence of SHR and to a lesser extent SCR.…”
Section: Radial Patterning In the Ground Tissuementioning
confidence: 99%